Nilai-Nilai Pendidikan Islam dalam Tradisi Turun Mandi di Kelurahan Tanah Garam Kota Solok - Husnul Khatimah; Ahmad Rivauzi (ISLAMIKA, 2022)
This research was carried out with the aim of knowing the history, process and values of Islamic education contained in the tradition of descending baths in Tanah Garam Village, Solok City.This type of research is qualitative using an ethnographic approach. Sources of data in this study are informants who come from religious leaders, traditional leaders, community leaders and the community of Tanah Garam Village, Solok City. Data collection techniques in this study through observation, interviews and documentation.From the results of the study, it can be concluded that the descending bathing tradition was carried out after the entry of Islam to Minangkabau. The implementation of the tradition of taking a bath as a form of obedience to Allah's command, namely aqikah. The series of descending bathing traditions begins with the procession of the mother bako, bathing the baby, stepping over the fire, smoking the baby and praying together. While the values of Islamic education contained in the descending bath tradition are the value of gratitude, the value of friendship, the value of mutual cooperation, the value of alms, the value of honoring guests, the value of caring, and the value of worship.